Estudo de revestimentos de superliga de níquel 625 em aços API com o processo de soldagem plasma pó de arco transferido - Oliveira, Davi de Santana de (2019)
GTAW-HW (Hot Wire Gas Tungsten Arc Welding) cladding process is widely used in the offshore industry, despite its low deposition rate and greater difficulty to control the level of dilution. The Plasma Powder Transferred Arc Welding (PPTAW) process is an alternative for internal cladding steel pipes to obtain increased corrosion resistance. This study presents tests to find the welding parameters for the PPTAW equipment used to allow the cladding of nickel 625 superalloy on API steel pipes meeting international standards requirements, such as thickness greater than 3 mm with a single cladding layer, dilution lower than 10%, iron content lower than 5% on the cladding surface and absence of cracks greater than 1.5 mm or pores larger than 2 mm. Macrography was performed to measure the thickness and dilution level of welded claddings, as well as optical microscopy at the sample interface to evaluate the defects. Iron content on the surface of the samples was analyzed by means of optical emission spectroscopy. The results showed that PPTAW equipment is capable of producing weld overlay that meet regulatory requirements.